Comparison of LC-MS/MS and EMIT methods for the precise determination of blood sirolimus in children with vascular anomalies - Zhao, Yue-Tao; Dai, Hao-Ran; Li, Yue; Zhang, Yuan-Yuan; Guo, Hong-Li; Ding, Xuan-Sheng; Hu, Ya-Hui; Chen, Feng (Frontiers in Pharmacology, 2022)
Sirolimus (SRL) is a mammalian target of rapamycin (mTOR) inhibitor. The whole blood concentration of SRL is routinely monitored to tailor dosage and prevent toxicity. Currently, the enzyme multiplied immunoassay technique (EMIT) is often applied to perform therapeutic drug monitoring (TDM) of SRL, but the cross-reactivity with various metabolites is of great concern. A more specific method is required, such as liquid chromatography-tandem mass spectrometry (LC-MS/MS). However, no study on the method comparison of EMIT and LC-MS/MS for the measurement of whole blood SRL concentration in children with vascular anomalies has been reported. This study developed a simple and sensitive LC-MS/MS assay for the determination of SRL. Meanwhile, consistency between LC-MS/MS and EMIT was evaluated by linear regression and Bland-Altman analysis. Whole blood samples were deproteinized with methanol for erythrocytes lysis and the resulting solution was injected into the LC-MS/MS system using the positive electrospray ionization mode. The multiple reaction monitoring transitions of m/z 931.7 → 864.6 and m/z 934.7 → 864.6 were used for SRL and SRL-d3 as the internal standard, respectively. The analytes were separated on a C18 column with a gradient mobile phase (0.1 mM formic acid and 0.05 mM ammonium acetate in methanol/ultrapure water). Blood samples collected from children with vascular anomalies undergoing SRL therapy were tested by EMIT and by LC-MS/MS. The linear range of LC-MS/MS was 0.500–50.0 ng/mL and that of EMIT was 3.50–30.0 ng/mL. A significant positive correlation between two assays was established with a regression equation described as [EMIT] = 1.281 × [LC−MS/MS] + 2.450 (r = 0.8361). Bland-Altman plots showed a mean concentration overestimation of 4.7 ng/mL (95% CI: [−3.1, 12.6]) and a positive bias of 63.1% (95% CI: [-36.1, 162.3]) generated by EMIT more than that of by LC-MS/MS. In conclusion, the two methods were closely correlated, indicating that switching between the two methods is feasible. Considering the overestimation nature of EMIT assay, switching from EMIT to LC-MS/MS method deserves close attention and necessary re-evaluation for the target therapeutic reference range may be required when methods switching within the same clinical lab or results comparing between different labs.